Characteristics of segments according to the preference system for job selection, opportunities for effective incentives in each employee group - Garai-Fodor, Mónika; Vasa, László; Jäckel, Katalin (Decision Making: Applications in Management and Engineering, 2023)
In addition to economic challenges, employers are also facing a growing generation gap. Generations that are significantly different in terms of values, mindsets and preferences need to be effectively managed in a workplace, which requires complex solutions. In this paper we present sub results of our primary research. In a quantitative procedure, we conducted a pre-tested standardized questionnaire online survey with random sample making method, resulting in 1146 evaluable questionnaires. Descriptive statistics to evaluate the results presented in this study. Descriptive statistics, and bivariate and multivariate analyses were applied to process the quantitative results, to test the hypotheses put forward. The main focus of our research is to investigate the factors that influence employees’ choice of jobs, and we analyzed the structure of their preference system. As a result of the research, we were able to identify distinct clusters according to the preference system of job selection. In the context of the resulting segments, we also analyzed which motivational tools could be most effective in encouraging higher performance. We believe that our research has useful implications for practice, by highlighting how to differentiate the pool of employees in terms of job choice and how to apply effective incentives to a specific segment.